2021
DOI: 10.3390/membranes11110862
|View full text |Cite
|
Sign up to set email alerts
|

CO2/CH4 and H2/CH4 Gas Separation Performance of CTA-TNT@CNT Hybrid Mixed Matrix Membranes

Abstract: This study explored the underlying synergy between titanium dioxide nanotube (TNT) and carbon nanotube (CNT) hybrid fillers in cellulose triacetate (CTA)-based mixed matrix membranes (MMMs) for natural gas purification. The CNT@TNT hybrid nanofillers were blended with CTA polymer and cast as a thin film by a facile casting technique, after which they were used for single gas separation. The hybrid filler-based membrane depicted a higher CO2 uptake affinity than the single filler (CNT/TNT)-based membrane. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…Figure 9 points out that CO 2 gas shows higher permeance compared to the CH 4 gas, because of the TFN hollow fiber membrane's high uptake affinity towards CO 2 than CH 4 . With the addition of nanofillers, because of their high surface area, tunable pore structure, as well as the presence of amine groups in the TFN membrane the solubility of CO 2 gas, becomes higher on the hollow fiber membrane surface shows high permeance 61 . At 1 bar pressure, the APTMSH@TFN‐3 membrane shows 22.3 GPU CO 2 permeance which is higher because the mobility of the polymer chain in a cross‐linked polymer structure increased at lower pressure resulting in the increased gas permeance at low pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 9 points out that CO 2 gas shows higher permeance compared to the CH 4 gas, because of the TFN hollow fiber membrane's high uptake affinity towards CO 2 than CH 4 . With the addition of nanofillers, because of their high surface area, tunable pore structure, as well as the presence of amine groups in the TFN membrane the solubility of CO 2 gas, becomes higher on the hollow fiber membrane surface shows high permeance 61 . At 1 bar pressure, the APTMSH@TFN‐3 membrane shows 22.3 GPU CO 2 permeance which is higher because the mobility of the polymer chain in a cross‐linked polymer structure increased at lower pressure resulting in the increased gas permeance at low pressure.…”
Section: Resultsmentioning
confidence: 99%
“…With the addition of nanofillers, because of their high surface area, tunable pore structure, as well as the presence of amine groups in the TFN membrane the solubility of CO 2 gas, becomes higher on the hollow fiber membrane surface shows high permeance. 61 At 1 bar pressure, the APTMSH@TFN-3 membrane shows 22.3 GPU CO 2 permeance which is higher because the mobility of the polymer chain in a cross-linked polymer structure increased at lower pressure resulting in the increased gas permeance at low pressure. It is found that in mixture gas separation the gas permeance is always lower compared to pure gas because of the competitive sorption between the gases.…”
Section: Mixed Water Vapor and N 2 Performance By Prepared Tfn Membranesmentioning
confidence: 98%
“…Consequently, the permeability of gases decreases in general. Conversely, the nature of TiO 2 fillers in our study has a high affinity toward CO 2 gas as they exhibit great adsorption capacity toward it 42 . The reduction in cluster size would also mean an increase in the effective surface area of particles, thereby suggesting the increase in permeability of CO 2 gases relative to CH 4 , as demonstrated in MF2.…”
Section: Resultsmentioning
confidence: 70%
“…Conversely, the nature of TiO 2 fillers in our study has a high affinity toward CO 2 gas as they exhibit great adsorption capacity toward it. 42 The reduction in cluster size would also mean an increase in the effective surface area of particles, thereby suggesting the increase in permeability of CO 2 gases relative to CH 4 , as demonstrated in MF2. On the other hand, the decrease in cluster amount and increase in average cluster size led to lower permeability values as observed in MT2 and MF3, possibly due to lesser effective filler surface area to interact with CO 2 gases.…”
Section: Influence Of Membrane Magnetization On Gas Separation Perfor...mentioning
confidence: 99%
“…11,12 Metal-organic frameworks (MOFs), known as porous particles with the potential to surpass the upper bound of Robeson, have been broadly utilized in mixed matrix membranes (MMMs) for gas separation [13][14][15] by developing new organic compounds such as molecular sieve materials, 16,17 silica, 18,19 covalent organic frameworks, [20][21][22] zeolites, [23][24][25] and carbon nanotubes. 26,27 Pebax 2533 consists of polyethylene oxide (PEO) soft and polyamide (PA) hard segments. It is also a type of water-swellable polymers (WSPs).…”
Section: Introductionmentioning
confidence: 99%